FAKTOR-FAKTOR PENDORONG KEBIASAAN JAJAN SISWA SMPN 13 KABUPATEN SIJUNJUNG - Asmawarti, Asmawarti; Yuliana, Yuliana; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims to identify the factors driving habit of eating snacks SMP N 13 district students Sijunjung internally by factors of knowledge, needs and attitudes of students, while externally based factors parents, friends and traders. This research is quantitative descriptive ekspolatif form. The study population was all students in SMP N 13 Sijunjung sitting in class VII and VIII as many as 207 people while a sample is determined by rando sampling technique with proportional sampling population 25% of the 51 students. Data collection technique is to use a questionnaire with Likert and Guttman scales. Descriptive data analysis using percentage calculations respondent achievement levels. Based on the survey results revealed the factors driving habits of students snack on internal factors to the knowledge students gained scores by 67% with the medium category, the needs of students by 81% with the high category, the attitude of 59% with poor category, the external factor of 70% with parents medium category, a friend by 80% with high category and traders by 71% with moderate category. Kata Kunci : Pendorong kebiasaan jajan, Makanan jajanan